PEMANFAATAN SALAK AFKIR SEBAGAI MEDIA PRODUKSI NATA DE SALACCA DI KABUPATEN BANJARNEGARA - Lukmanul Hakim; Bondan Hary Setiawan (Jurnal Ilmiah Media Agrosains, 2014)
Off grade salacca still contain many nutritions that potencially used as fermentation media on nata (nata de salacca) production. This research purpose is to know the ability of off grade salacca in Banjarnegara district as raw material on nata de salacca production. The research was conducted in Agriculture Product Processing laboratory of Agrotechnology Department on Banjarnegara Politechnic at September-November 2012. This research used randomized block design with four variable. That variable are variation of sugar added (0% (control), 5%, 8%, and 11%). Parameter that was observed are thickness and weight of nata de salacca. The result showed that off grade salacca can be used as fermentation media on nata de salacca production. The best result was conducted by 8% sugar added that can produced 8 mm thickness and 800 g weight of nata de salacca.